Uncharted Waters: Addressing the Regulatory Gaps in Part VII of UNCLOS in the Advent of Maritime Autonomous Surface Ships - Aronen, Arttu (My University, 2026)
This bachelor’s thesis examines the regulatory gaps in the United Nations Convention on the Law of the Sea in relation to the new technological innovation of Maritime Autonomous Surface Ships. The role of the Convention is important as it provides the general framework for all maritime operations. The autonomous nature of these modern vessels challenges the human-centric assumptions of the old Convention and prompts the need to re-evaluate its provisions in light of the new technological advancements. By analysing the provisions regarding general maritime principles and piracy in Part VII of UNCLOS, the thesis seeks to answer the question of whether or not the Convention remains an adequate legal instrument for regulating maritime operations in the advent of autonomous vessels. To aid in this task, the study employs the critical doctrinal method ‘Gaps, Conflicts and Ambiguities’ by Jorge L. Esquirol. The legal gaps that are discovered are reconciled through different forms of legal interpretation. The study found that while the shift to autonomous shipping creates gaps and ambiguities in the existing law of the sea regime, UNCLOS remains an adequate legal instrument for regulating maritime activities. The Convention therefore maintains its status as a framework convention for the law of the sea.

Tämä ON-tutkielma tarkastelee itseohjautuvien laivojen aiheuttamia sääntelyaukkoja Yhdistyneiden kansakuntien merioikeusyleissopimuksessa. Yleissopimuksella on tärkeä merkitys merenkulun toimintoja käsittelevänä yleisenä puitesopimuksena. Nykyaikaisten alusten autonominen luonne haastaa vanhalle yleissopimukselle ominaisia ihmiskeskeisiä oletuksia ja luo tarpeen arvioida sen määräyksiä uudelleen teknologian kehityksen valossa. Tarkastelemalla yleissopimuksen VII–osan säännöksiä yleisistä merioikeudellisista periaatteista ja merirosvoudesta, tutkielma pyrkii vastaamaan kysymykseen siitä, onko yleissopimus riittävä oikeudellinen instrumentti merenkulun sääntelyyn itseohjautuvien laivojen yleistyessä. Tarkastelun tukena käytetään Jorge L. Esquirolin kriittistä metodia ’Gaps, Conflicts and Ambiguities’. Havaitut lain epäselvyydet pyritään ratkaisemaan oikeudellisen tulkinnan keinojen avulla. Tutkimus osoitti, että vaikka siirtyminen autonomiseen merenkulkuun luo aukkoja ja epäselvyyksiä nykyiseen merioikeusjärjestelmään, UNCLOS säilyy riittävänä oikeudellisena instrumenttina yleisluontoiseen merenkulun toimintojen sääntelyyn. Yleissopimus säilyttää siten asemansa merenkulkua koskevana puitesopimuksena.
Keywords: law of the sea, autonomous vessels, international conventions, legal principles, piracy, merioikeus, itseohjautuvat laivat, kansainväliset sopimukset, oikeusperiaatteet, merirosvous